(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The high incidence of diabetes mellitus in Indonesia can be caused by an unhealthy diet. One of the management of diabetes diet by eating high-fiber foods. This study aims to determine the formulation of a snack bar made from chickpea flour, soybean pulp flour, and pumpkin seeds and to analyze the nutritional value of a high-fiber snack bar as a snack for people with type 2 diabetes mellitus. This study used a non-factorial completely randomized design with 3 formulations high-fiber snack bars. The selected formula was determined by acceptance test by semi-trained panelists analyzed by univariate and friedman test. The chosen formula, F2, was carried out in a laboratory analysis with the results of a proximate analysis of a high fiber snack bar per 100 grams with a water content of 4.92 percent, ash content 5.16 percent, protein content 33.64 percent, fat content 28.78 percent, and carbohydrates 27.59 percent, analysis of high fiber snack bar food fiber 21.75 percent and qualitative analysis of high fiber snack bar flavonoid negative (-). Snack bar formula F2 with chickpea flour, soybean pulp flour and pumpkin seeds can be recommended as a snack for people with diabetes mellitus because of its high fiber content (21.75%/100 grams).